2016
DOI: 10.1111/jtxs.12214
|View full text |Cite
|
Sign up to set email alerts
|

Steady, dynamic and structural deformation (three interval thixotropy test) characteristics of gluten‐free Tarhana soup prepared with different concentrations of quinoa flour

Abstract: Malnutrition is currently widespread in many areas of the world. Therefore, it must be focused on the cheap, but nutritious plant protein and mineral sources, such as legume and cereals. Several recent studies have showed the successful formulation of pseudocereal containing cereal based products. Tarhana is a traditional fermented food made of mainly a mixture cereal and yoghurt. Tarhana or tarhana-like products have been enriched or replaced with cereal and pseudocereal. In this research, the applicability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…(2013) reported similar rheological shear‐thinning, weak gel‐like behavior of a cornstarch thickener as observed in PS‐ and QF‐thickened soups (Mackley et al., 2013). Furthermore, the same rheological behavior was demonstrated in Tarhana soup with different concentrations of QF (Demir, Kutlu, & Yilmaz, 2017). Although starch‐ and gum‐based thickeners have differences in sensory attributes of texture and mouthfeel, their rheological behavior is similar at IDDSI level 2.…”
Section: Discussionsupporting
confidence: 55%
“…(2013) reported similar rheological shear‐thinning, weak gel‐like behavior of a cornstarch thickener as observed in PS‐ and QF‐thickened soups (Mackley et al., 2013). Furthermore, the same rheological behavior was demonstrated in Tarhana soup with different concentrations of QF (Demir, Kutlu, & Yilmaz, 2017). Although starch‐ and gum‐based thickeners have differences in sensory attributes of texture and mouthfeel, their rheological behavior is similar at IDDSI level 2.…”
Section: Discussionsupporting
confidence: 55%
“…In another study, used under size bulgur in couscous formulation and found that protein contents were higher than control sample (Yüksel et al 2017). Moreover, recent research highlights a significant trend where raw products, such as pseudo-cereals, play a crucial role in enhancing and diversifying formulations of gluten-containing products (Demir et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…This approach has been applied to thixotropic fluids by studying particle interaction strengths, explicitly concerning the gradual breakdown and rebuilding of solid dispersed structures. 19,27,28 In our previous research, we introduced multiple interval thixotropy tests (miTT) to check how different shear rates influence the rheological properties. 29 The miTT profile set a series of shear rate ramps to destroy the sample and after each specific shear, identical time sweep intervals were used to monitor structural recovery.…”
Section: Introductionmentioning
confidence: 99%